2019
DOI: 10.1007/s00420-019-01496-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the pattern of shift work and sleep disturbances in Korean firefighters

Abstract: Purpose Sleep disturbances are prevalent in firefighters, but the relationship between patterns of shift work and sleep disturbances has not yet been investigated. Here, this relationship has been evaluated in Korean firefighters. Methods A cross-sectional study was conducted using an online questionnaire, which captured demographic, psychosocial and work-related characteristics. Sleep disturbance was assessed using the insomnia severity index (ISI). The relationship between insomnia and work-related factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 30 publications
(31 reference statements)
3
36
1
1
Order By: Relevance
“…In addition, the insomnia risk was significantly increased in the case of feeling much of physical burden during firefighting work (high subjective OPA) and if the frequency of occupational activities was ≥5 times a week. These results are consistent with previous studies according to which a high level of OPA and working long hours significantly increased the sleep disturbance risk [ 11 , 21 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In addition, the insomnia risk was significantly increased in the case of feeling much of physical burden during firefighting work (high subjective OPA) and if the frequency of occupational activities was ≥5 times a week. These results are consistent with previous studies according to which a high level of OPA and working long hours significantly increased the sleep disturbance risk [ 11 , 21 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that the shiftwork itself is not only associated with high OPA [ 21 , 32 ], but can also cause insomnia by disrupting the circadian rhythm [ 33 ]. However, the results of this study show that shift work does not significantly affect insomnia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations